2022
DOI: 10.1101/2022.01.14.22269290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional healthy brain activity, glioma occurrence and symptomatology

Abstract: It is unclear why exactly gliomas show preferential occurrence in certain brain areas. Increased spiking activity around gliomas leads to faster tumor growth in animal models, while higher non-invasively measured brain activity is related to shorter survival in patients. However, it is unknown how regional intrinsic brain activity, as measured in healthy controls, relates to glioma occurrence. We first investigated whether gliomas occur more frequently in regions with intrinsically higher brain activity. Secon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…48 At the macroscale circuit level, Numan et al ( 2022) describes gliomas with increased malignancy preferentially occurring in regions characterized by higher brain activity in human controls. 49 Functional brain networks have also been implicated as the substrate for structural lesions in a wide variety of psychiatry disorders, and appear to influence the location of primary tumours, albeit with a reduced effect size relative to genetic co-expression. 16 Additionally, tumour functional integration within the global brain signal has been linked with cognitive recovery after glioma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…48 At the macroscale circuit level, Numan et al ( 2022) describes gliomas with increased malignancy preferentially occurring in regions characterized by higher brain activity in human controls. 49 Functional brain networks have also been implicated as the substrate for structural lesions in a wide variety of psychiatry disorders, and appear to influence the location of primary tumours, albeit with a reduced effect size relative to genetic co-expression. 16 Additionally, tumour functional integration within the global brain signal has been linked with cognitive recovery after glioma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…46 At the macroscale circuit level, Numan et al (2022) describes gliomas with increased malignancy preferentially occurring in regions characterized by higher brain activity in human controls. 47 Functional brain networks have also been implicated as the substrate for structural lesions in a wide variety of psychiatry disorders, and appear to influence the location of primary tumours, albeit with a reduced effect size relative to genetic co-expression. 15 Additionally, tumour functional integration within the global brain signal has been linked with cognitive recovery after glioma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it will be important to monitor subclinical neuronal hyperexcitability as this might still affect glioma growth which will require further examination via longitudinal monitoring via EEG and MEG [38]. Additionally, it has been recently reported that gliomas occur more often in brain regions with higher activity [79].…”
Section: A Potential Vicious Circle Of Neuronal Hyperexcitability And...mentioning
confidence: 99%